Preventing Violence Against Women and Children: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Violence against women and children is a serious public health concern, with costs at multiple levels of society. Although violence is a threat to everyone, women and children are particularly susceptible to victimization because they often have fewer rights or lack appropriate means of protection. In some societies certain types of violence are deemed socially or legally acceptable, thereby contributing further to the risk to women and children. In the past decade research has documented the growing magnitude of such violence, but gaps in the data still remain. Victims of violence of any type fear stigmatization or societal condemnation and thus often hesitate to report crimes. The issue is compounded by the fact that for women and children the perpetrators are often people they know and because some countries lack laws or regulations protecting victims. Some of the data that have been collected suggest that rates of violence against women range from 15 to 71 percent in some countries and that rates of violence against children top 80 percent. These data demonstrate that violence poses a high burden on global health and that violence against women and children is common and universal. Preventing Violence Against Women and Children focuses on these elements of the cycle as they relate to interrupting this transmission of violence. Intervention strategies include preventing violence before it starts as well as preventing recurrence, preventing adverse effects (such as trauma or the consequences of trauma), and preventing the spread of violence to the next generation or social level. Successful strategies consider the context of the violence, such as family, school, community, national, or regional settings, in order to determine the best programs.

Clinical Preventive Services for Women: Closing the Gaps - Institute of Medicine (The National Academies Press, 2011)
Women suffer disproportionate rates of chronic disease and disability from some conditions, and often have high out-of-pocket health care costs. The passage of the Patient Protection and Affordable Care Act of 2010 (ACA) provides the United States with an opportunity to reduce existing health disparities by providing an unprecedented level of population health care coverage. The expansion of coverage to millions of uninsured Americans and the new standards for coverage of preventive services that are included in the ACA can potentially improve the health and well-being of individuals across the United States. Women in particular stand to benefit from these additional preventive health services. Clinical Preventive Services for Women reviews the preventive services that are important to women's health and well-being. It recommends that eight preventive health services for women be added to the services that health plans will cover at no cost. The recommendations are based on a review of existing guidelines and an assessment of the evidence on the effectiveness of different preventive services. The services include improved screening for cervical cancer, sexually transmitted infections, and gestational diabetes; a fuller range of contraceptive education, counseling, methods, and services; services for pregnant women; at least one well-woman preventive care visit annually; and screening and counseling for interpersonal and domestic violence, among others. Clinical Preventive Services for Women identifies critical gaps in preventive services for women as well as measures that will further ensure optimal health and well-being. It can serve as a comprehensive guide for federal government agencies, including the Department of Health and Human Services and the Center for Disease Control and Prevention; state and local government agencies; policy makers; health care professionals; caregivers, and researchers.

Threatening Communications and Behavior: Perspectives on the Pursuit of Public Figures - National Research Council (The National Academies Press, 2011)
Today's world of rapid social, technological, and behavioral change provides new opportunities for communications with few limitations of time and space. Through these communications, people leave behind an ever-growing collection of traces of their daily activities, including digital footprints provided by text, voice, and other modes of communication. Meanwhile, new techniques for aggregating and evaluating diverse and multimodal information sources are available to security services that must reliably identify communications indicating a high likelihood of future violence. In the context of this changed and changing world of communications and behavior, the Board on Behavioral, Cognitive, and Sensory Sciences of the National Research Council presents this volume of three papers as one portion of the vast subject of threatening communications and behavior. The papers review the behavioral and social sciences research on the likelihood that someone who engages in abnormal and\/or threatening communications will actually then try to do harm. The focus is on how the scientific knowledge can inform and advance future research on threat assessments, in part by considering the approaches and techniques used to analyze communications and behavior in the dynamic context of today's world. The papers in the collection were written within the context of protecting high-profile public figures from potential attach or harm. The research, however, is broadly applicable to U.S. national security including potential applications for analysis of communications from leaders of hostile nations and public threats from terrorist groups. This work highlights the complex psychology of threatening communications and behavior, and it offers knowledge and perspectives from multiple domains that contribute to a deeper understanding of the value of communications in predicting and preventing violent behaviors.

Cognitive Rehabilitation Therapy for Traumatic Brain Injury: Evaluating the Evidence - Institute of Medicine
Traumatic brain injury (TBI) may affect 10 million people worldwide. It is considered the \

Research Training in the Biomedical, Behavioral, and Clinical Research Sciences - National Research Council (The National Academies Press, 2011)
Comprehensive research and a highly-trained workforce are essential for the improvement of health and health care both nationally and internationally. During the past 40 years the National Research Services Award (NRSA) Program has played a large role in training the workforce responsible for dramatic advances in the understanding of various diseases and new insights that have led to more effective and targeted therapies. In spite of this program, the difficulty obtaining jobs after the postdoc period has discouraged many domestic students from pursuing graduate postdoc training. In the United States, more than 50 percent of the postdoc workforce is made up of individuals who obtained their Ph.D.s from other countries. Indeed, one can make a strong argument that the influx of highly trained and creative foreigners has contributed greatly to U.S. science over the past 70 years. Research Training in the Biomedical, Behavioral, and Clinical Research Sciences discusses a number of important issues, including: the job prospects for postdocs completing their training; questions about the continued supply of international postdocs in an increasingly competitive world; the need for equal, excellent training for all graduate students who receive NIH funding; and the need to increase the diversity of trainees. The book recommends improvements in minority recruiting, more rigorous and extensive training in the responsible conduct of research and ethics, increased emphasis on career development, more attention to outcomes, and the requirement for incorporating more quantitative thinking in the biomedical curriculum.

Modeling the Economics of Greenhouse Gas Mitigation: Summary of a Workshop - National Research Council (The National Academies Press, 2011)
Models are fundamental for estimating the possible costs and effectiveness of different policies for reducing greenhouse gas (GHG) emissions. There is a wide array of models to perform such analysis, differing in the level of technological detail, treatment of technological progress, spatial and sector details, and representation of the interaction of the energy sector to the overall economy and environment. These differences impact model results, including cost estimates. More fundamentally, these models differ as to how they represent fundamental processes that have a large impact on policy analysis–such as how different models represent technological learning and cost reductions that come through increasing production volumes, or how different models represent baseline conditions. Reliable estimates of the costs and potential impacts on the United States economy of various emissions reduction and other mitigation strategies are critical to the development of the federal climate change research and development portfolio. At the request of the U.S. Department of Energy (DOE), the National Academies organized a workshop, summarized in this volume, to consider some of these types of modeling issues.

Evaluating Testing, Costs, and Benefits of Advanced Spectroscopic Portals: Final Report (Abbreviated Version) - National Research Council (The National Academies Press, 2011)
This letter is the abbreviated version of an update of the interim report on testing, evaluation, costs, and benefits of advanced spectroscopic portals (ASPs), issued by the National Academies' Committee on Advanced Spectroscopic Portals in June 2009 (NRC 2009). This letter incorporates findings of the committee since that report was written, and it sharpens and clarifies the messages of the interim report based on subsequent committee investigations of more recent work by the Domestic Nuclear Detection Office (DNDO). The key messages in this letter, which is the final report from the committee, are stated briefly in the synopsis on the next page and described more fully in the sections that follow. The committee provides the context for this letter, and then gives advice on: testing, evaluation, assessing costs and benefits, and deployment of advanced spectroscopic portals. The letter closes with a reiteration of the key points. The letter is abbreviated in that a small amount of information that may not be released publicly for security or law-enforcement reasons has been redacted from the version delivered to you in October 2010, but the findings and recommendations remain intact.

Structural Integrity of Offshore Wind Turbines: Oversight of Design, Fabrication, and Installation - Special Report 305 - Transportation Research Board (The National Academies Press, 2011)
TRB Special Report 305: Structural Integrity of Offshore Wind Turbines: Oversight of Design, Fabrication, and Installation explores the U.S. Department of the Interior's Bureau of Ocean Energy Management, Regulation, and Enforcement (BOEMRE) approach to overseeing the development and safe operation of wind turbines on the outer continental shelf, with a focus on structural safety. The committee that developed the report recommended that in order to facilitate the orderly development of offshore wind energy and support the stable economic development of this nascent industry, the United States needs a set of clear requirements that can accommodate future design development. The report recommends that BOEMRE develop a set of requirements that establish goals and objectives with regard to structural integrity, environmental performance, and energy generation. The committee found that the risks to human life and the environment associated with offshore wind farms are substantially lower than for other industries such as offshore oil and gas, because offshore wind farms are primarily unmanned and contain minimal quantities of hazardous substances. This finding implies that an approach with significantly less regulatory oversight may be taken for offshore wind farms. Under this approach, industry would be responsible for proposing sets of standards, guidelines, and recommended practices that meet the performance requirements established by BOEMRE. The domestic industry can build on standards, guidelines, and practices developed in Europe, where the offshore wind energy is further developed, but will have to fill gaps such as the need to address wave and wind loadings encountered in hurricanes. The report also includes findings and recommendations about the role that certified verification agents (third party evaluators) can play in reviewing packages of standards and project-specific proposals.

Practices to Protect Bus Operators from Passenger Assault - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s Transit Cooperative Research Program (TCRP) Synthesis 93: Practices to Protect Bus Operators from Passenger Assault highlights practices and policies implemented by transit agencies to deter and mitigate assaults on bus operators.

Sociocultural Data to Accomplish Department of Defense Missions: Toward a Unified Social Framework: Workshop Summary - National Research Council (The National Academies Press, 2011)
Sociocultural Data to Accomplish Department of Defense Missions: Toward a Unified Social Framework summarizes presentations and discussions that took place on August 16-17, 2010, at a National Research Council public workshop sponsored by the Office of Naval Research. The workshop addressed the variables and complex interaction of social and cultural factors that influence human behavior, focusing on potential applications to the full spectrum of military operations. The workshop's keynote address by Major General Michael T. Flynn, U.S. Army, provided critical context about the cultural situation and needs of the military operating in Afghanistan. Additional presentations were divided into four panels to address the diverse missions encountered by the U.S. military worldwide. The workshop concluded with a final panel to discuss the strengths and weaknesses of different methods of acquiring and using relevant data and knowledge to accomplish these missions. The panel topics and presenters are listed below: Conflict Is Local: Mapping the Sociocultural Terrain David Kennedy, Hsinchun Chen, and Kerry Patton Bridging Sociocultural Gaps in Cooperative Relationships Robert Rubinstein, Alan Fiske, and Donal Carbaugh Building Partner Capacity with Sociocultural Awareness Jeffrey Sanchez-Burks and Shinobu Kitayama The Art of Sociocultural Persuasion Jeanne Brett, James Dillard, and Brant R. Burleson Tools, Methods, Frameworks, and Models Mark Bevir, Laura A. McNamara, Robert G. Sargent, and Jessica Glicken Turnley

State and Local Policy Initiatives to Reduce Health Disparities: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Although efforts to reduce health disparities receive attention at the national level, information on the successes of state and local efforts are often not heard. On May 11, 2009, the Institute of Medicine held a public workshop to discuss the role of state and local policy initiatives to reduce health disparities. The workshop brought together stakeholders to learn more about what works in reducing health disparities and ways to focus on localized efforts when working to reduce health disparities.

The Health of Lesbian, Gay, Bisexual, and Transgender People: Building a Foundation for Better Understanding - Institute of Medicine (The National Academies Press, 2011)
At a time when lesbian, gay, bisexual, and transgender individuals2014often referred to under the umbrella acronym LGBT2014are becoming more visible in society and more socially acknowledged, clinicians and researchers are faced with incomplete information about their health status. While LGBT populations often are combined as a single entity for research and advocacy purposes, each is a distinct population group with its own specific health needs. Furthermore, the experiences of LGBT individuals are not uniform and are shaped by factors of race, ethnicity, socioeconomic status, geographical location, and age, any of which can have an effect on health-related concerns and needs. The Health of Lesbian, Gay, Bisexual, and Transgender People assesses the state of science on the health status of LGBT populations, identifies research gaps and opportunities, and outlines a research agenda for the National Institute of Health. The report examines the health status of these populations in three life stages: childhood and adolescence, early\/middle adulthood, and later adulthood. At each life stage, the committee studied mental health, physical health, risks and protective factors, health services, and contextual influences. To advance understanding of the health needs of all LGBT individuals, the report finds that researchers need more data about the demographics of these populations, improved methods for collecting and analyzing data, and an increased participation of sexual and gender minorities in research. The Health of Lesbian, Gay, Bisexual, and Transgender People is a valuable resource for policymakers, federal agencies including the National Institute of Health (NIH), LGBT advocacy groups, clinicians, and service providers.

Toward an Integrated Science of Research on Families: Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Demographic changes, immigration, economic upheavals, and changing societal mores are creating new and altered structures, processes, and relationships in American families today. As families undergo rapid change, family science is at the brink of a new and exciting integration across methods, disciplines, and epistemological perspectives. The purpose of The Science of Research on Families: A Workshop, held in Washington, DC, on July 13-14, 2010, was to examine the broad array of methodologies used to understand the impact of families on children's health and development. It sought to explore individual disciplinary contributions and the ways in which different methodologies and disciplinary perspectives could be combined in the study of families. Toward an Integrated Science of Research on Families documents the information presented in the workshop presentations and discussions. The report explores the idea of family research as being both basic and applied, offering opportunities for learning as well as intervention. It discusses research as being most useful when organized around particular problems, such as obesity or injury prevention. Toward an Integrated Science of Research on Families offers a problem-oriented approach that can guide a broad-based research program that extends across funders, institutions, and scientific disciplines.

Informing the Future: Critical Issues in Health, Sixth Edition - Institute of Medicine (The National Academies Press, 2011)
This report illustrates the work of IOM committees in selected, major areas in recent years, followed by a description of IOM's convening and collaborative activities and fellowship programs. The last section provides a comprehensive bibliography of IOM reports published since 2007.

Women’s Issues in Transportation: Summary of the 4th International Conference, Volume 1: Conference Overview and Plenary Papers - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s Conference Proceedings 46: Women2019s Issues in Transportation: Summary of the 4th International Conference, Volume 1: Conference Overview and Plenary Papers includes an overview of the October 2009 conference and six commissioned resource papers, including the two keynote presentations. Women2019s Issues in Transportation: Summary of the 4th International Conference, Volume 2: Technical Papers includes 27 full peer-reviewed papers that were presented at the October 2009 conference. The conference highlighted the latest research on changing demographics that affect transportation planning, programming, and policy making, as well as the latest research on crash and injury prevention for different segments of the female population. Special attention was given to pregnant and elderly transportation users, efforts to better address and increase women2019s personal security when using various modes of transportation, and the impacts of extreme events such as hurricanes and earthquakes on women2019s mobility and that of those for whom they are responsible.

Increasing National Resilience to Hazards and Disasters: The Perspective from the Gulf Coast of Louisiana and Mississippi: Summary of a Workshop - Steve Olson (The National Academies Press, 2011)
Natural disasters are having an increasing effect on the lives of people in the United States and throughout the world. Every decade, property damage caused by natural disasters and hazards doubles or triples in the United States. More than half of the U.S. population lives within 50 miles of a coast, and all Americans are at risk from such hazards as fires, earthquakes, floods, and wind. The year 2010 saw 950 natural catastrophes around the world–the second highest annual total ever–with overall losses estimated at 130 billion. The increasing impact of natural disasters and hazards points to increasing importance of resilience, the ability to prepare and plan for, absorb, recover from, or more successfully adapt to actual or potential adverse events, at the individual , local, state, national, and global levels. Assessing National Resilience to Hazards and Disasters reviews the effects of Hurricane Katrina and other natural and human-induced disasters on the Gulf Coast of Louisiana and Mississippi and to learn more about the resilience of those areas to future disasters. Topics explored in the workshop range from insurance, building codes, and critical infrastructure to private-sector issues, public health, nongovernmental organizations and governance. This workshop summary provides a rich foundation of information to help increase the nation's resilience through actionable recommendations and guidance on the best approaches to reduce adverse impacts from hazards and disasters.

Hunger and Obesity: Understanding a Food Insecurity Paradigm: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
At some point during 2009, more than 17 million households in the United States had difficulty providing enough food for all their members because of a lack of resources. In more than one-third of these households, the food intake of some household members was reduced and normal eating patterns were disrupted due to limited resources. The Workshop on Understanding the Relationship Between Food Insecurity and Obesity was held to explore the biological, economic, psychosocial, and other factors that may influence the relationship between food insecurity, overweight, and obesity in the United States. Hunger and Obesity examines current concepts and research findings in the field. The report identifies information gaps, proposes alternative approaches to analyzing data, recommends new data that should be collected, and addresses the limitations of the available research.

Reference Manual on Scientific Evidence: Third Edition - National Research Council (The National Academies Press, 2011)
The Reference Manual on Scientific Evidence, Third Edition, assists judges in managing cases involving complex scientific and technical evidence by describing the basic tenets of key scientific fields from which legal evidence is typically derived and by providing examples of cases in which that evidence has been used. First published in 1994 by the Federal Judicial Center, the Reference Manual on Scientific Evidence has been relied upon in the legal and academic communities and is often cited by various courts and others. Judges faced with disputes over the admissibility of scientific and technical evidence refer to the manual to help them better understand and evaluate the relevance, reliability and usefulness of the evidence being proffered. The manual is not intended to tell judges what is good science and what is not. Instead, it serves to help judges identify issues on which experts are likely to differ and to guide the inquiry of the court in seeking an informed resolution of the conflict. The core of the manual consists of a series of chapters (reference guides) on various scientific topics, each authored by an expert in that field. The topics have been chosen by an oversight committee because of their complexity and frequency in litigation. Each chapter is intended to provide a general overview of the topic in lay terms, identifying issues that will be useful to judges and others in the legal profession. They are written for a non-technical audience and are not intended as exhaustive presentations of the topic. Rather, the chapters seek to provide judges with the basic information in an area of science, to allow them to have an informed conversation with the experts and attorneys.

Public Transportation Systems as the Foundation for Economic Growth - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s Transit Cooperative Research Program (TCRP) RRD 102: Public Transportation Systems as the Foundation for Economic Growth examines how transit investments are linked to economic growth and recovery in several cities in Turkey, Egypt, and South Africa.

The Science of Adolescent Risk-Taking: Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Adolescence is a time when youth make decisions, both good and bad, that have consequences for the rest of their lives. Some of these decisions put them at risk of lifelong health problems, injury, or death. The Institute of Medicine held three public workshops between 2008 and 2009 to provide a venue for researchers, health care providers, and community leaders to discuss strategies to improve adolescent health.